Gerakan Pesantren Sehat di Pondok Pesantren Darul Mukhlisin Kota Malang - Asri, Yuni; Priasmoro, Dian Pitaloka; Ardiyanti, Sahda Eka (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Health is an important aspect of daily life, including in islamic boarding school environments which play a significant role in religious and moral education. The Healthy Pesantren Movement at Darul Mukhlisin Islamic Boarding School in Sawojajar, Kedungkandang Subdistrict, Malang City, aims to improve the health of students through various programs and activities. This community service program is carried out over 1 year, starting in August 2023 and continuing until 2024, involving 60 students. The program includes health check-ups, health education on Clean and Healthy Living Behavior (PHBS), and improved environmental sanitation. Through a participatory approach, students and pesantren administrators are encouraged to actively engage in maintaining and improving personal and environmental health. The results of this program show an increase in health awareness and healthy living behaviors among students, as well as improvements in sanitation conditions in the pesantren environment. This movement is expected to serve as a model for other pesantren in efforts to enhance the health and well-being of students comprehensively.